ChemInform Abstract: Efficient Synthesis of 1, 4‐Disubstituted Triazolyl N‐Carboxamides via a Simple and Convenient MCR Using Basic Alumina as Solid Support. Issue 4 (28th January 2014) - Pal, Rammyani; Sarkar, Swarbhanu; Chatterjee, Nivedita; Sen, Asish Kumar
Abstract The synthesis of the title compounds involves in situ formation of organic azides, 1, 3‐dipolar cycloaddition of the latter with terminal alkynes and amide or ester bond formation.